Konsep Shulh: Penyelesaian Sengketa Produk Tepat Pembiayaan Syariah Btpn Syariah - Rahmat Husein Lubis (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2023)
This research originated from a dispute that occurred at BTPN Syariah MMS Siabu on the Right Sharia Financing product. Researchers want to examine how the solution to these problems can be solved with the Shulh Concept. This research is qualitative research where the type of empirical legal research. The data analysis technique in this research, namely by collecting data, then the data is recorded, then it will be presented in the form of a narrative conclusion. The conclusion from this study is that the cause of this dispute occurs because when providing data on prospective customers it is not transparent, dishonesty of information, then problems with economic conditions, and the circumstances of the customer's family are appropriate for the sharia financing. Then for the pattern that is the right product of sharia financing by means of the Shulh concept, namely by the way the local village head presents both parties and discusses the origin of the problem, then all forms of debt left by the wife are repaid by the husband by making a black and white agreement reinforced with a stamp.